1980
DOI: 10.1159/000260461
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Translocation between Enamel and Streptococcus mutans in the Presence of Sucrose and Fluoride with Observations on the Acid Phosphatase of S. mutans

Abstract: Intact cells of Streptococcus mutans K-1 were incubated with enamel powder in buffer, pH 5.8, saturated with enamel salts, the cells or the enamel having been previously labelled with 32P. The cells were also incubated with p-nitrophenyl phosphate at varying pH or at pH 4.8 with varying concentrations of fluoride. Incubation of the K-1 cells with 32P-labelled enamel caused an equilibration of enamel 32P within the cells. During sucrose fermentation, the uptake of enamel 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…On a comparative basis, at the end of 23 h of incubation, S. salivarius cell suspension showed the highest activity for MFP hydrolysis (umol MFP decomposed/mg protein) followed by those of S. mitis, and S. mutans, BHT. Our data for optimum MFPase activity was basically similar to those reported for p-nitrophenyl phosphatase (pH 4.8), and salivary phos phatase activity (pH 5.4) [Greenman and Melville, 1978;Luoma, 1980], but differ ent from that of the streptococcus strain, KIR (pH 7.00) reported by Jackson [1982], Figure 1 also shows that regardless of strain, MFPase hydrolysis activities in vitro fell to significantly lower levels at pH values deviating from the observed optimum. An interesting observation on pH at this point is that the conditions for maximal hydrolysis of MFP appear to coincide with the lower pH values which could occur especially after ingestion of sugar-containing meals, and conse quently the prevalence of caries.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…On a comparative basis, at the end of 23 h of incubation, S. salivarius cell suspension showed the highest activity for MFP hydrolysis (umol MFP decomposed/mg protein) followed by those of S. mitis, and S. mutans, BHT. Our data for optimum MFPase activity was basically similar to those reported for p-nitrophenyl phosphatase (pH 4.8), and salivary phos phatase activity (pH 5.4) [Greenman and Melville, 1978;Luoma, 1980], but differ ent from that of the streptococcus strain, KIR (pH 7.00) reported by Jackson [1982], Figure 1 also shows that regardless of strain, MFPase hydrolysis activities in vitro fell to significantly lower levels at pH values deviating from the observed optimum. An interesting observation on pH at this point is that the conditions for maximal hydrolysis of MFP appear to coincide with the lower pH values which could occur especially after ingestion of sugar-containing meals, and conse quently the prevalence of caries.…”
Section: Resultssupporting
confidence: 87%
“…To explain the underlying action of this pop ular active ingredient widely formulated in commercial dentifrices, the following theories are presented: (1) that F~ ions re leased from MFP, by either chemical de gradation [Gron et al, 1971;Pearce, 1974], or enzymic breakdown via phosphatases in saliva [Pearce and Jenkins, 1977], in plaque [Ericsson, 1967;Jackson, 1982], and in certain aciduric oral microorgan isms [Fitzgerald, 1952], particularly within the outer structures of Streptococcus mu tans [Luoma, 1980], ultimately provide the cariostatic action; (2) that PCLF2' of MFP exchanges directly with orthophosphate groups of hydroxyapatite increasing en amel resistance to acid dissolution [In gram, 1973]; and (3) that intracrystalline transposition occurs following PO3 F2' ex change to form the less soluble fluoroapatite [Ericsson, 1967], In any case, a better understanding of the basic mechanism of action should benefit immeasurably the formulation of more effective dentifrices regardless of whether the anticaries action of MFP is mainly mediated by PC>3 2' or F'. The purpose of this study was to further investigate the ability of oral streptococci and pooled, unstimulated saliva to hydro lyze MFP, liberating F".…”
mentioning
confidence: 99%
“…In addition, it is possible that Pi was transported into the cells and incorporated into metabolic intermedi ates. Indeed, Luoma [1980] demonstrated the uptake of 32P into sucrose-fermenting cells of S. mutans K-l from radiolabelled enamel in an in vitro system. Iwami and Yamada [1980], however, showed that esterification of intracellular Pi varied with pH of the medium.…”
Section: Enamel As a Source O F Plaque Ca And Pimentioning
confidence: 99%
“…Without this additional phosphorus, the fluid phase covering the enamel may have re mained unsaturated wiht OH-apatite, allowing more apatite to be released from the subsurface enamel [Larsen et al, 1976]. Furthermore, participation of bacterial phosphate in rehardening of enamel in vitro has been reported [Luoma, 1975[Luoma, , 1980. The protective effects observed in the Fh group were all clearly stronger than in the F group where the fluoride var nish was acting alone.…”
Section: Application Of Fluoride Varnish Combined With the Added Fluomentioning
confidence: 99%
“…Mg, and P contents of Streptococcus sobrinus because bacterial electrolyte transfers [Rosen, 1978], espe cially that of phosphate, may modify the enamel-pro tective properties of the adjacent fluid [Luoma, 1975[Luoma, , 1980, An essential new aspect was a 10-day incuba tion period instead of the previous 1 -day period.…”
mentioning
confidence: 99%